Sistema de rastreamento e controle de recursos de um veículo utilizando um smartphone android - Galon, Handrey Emanuel (2014)
Since the dawn, the humanity sought ways to locate on the globe quickly and effectively. Modern society also requires that people are constantly connected in order that information is shared quickly. This paper proposes a prototype involving hardware and software, for the development of a platform for vehicle tracking. The user's software was developed using the Android platform, aiming its use in smartphones. To drive and data recovery in the vehicle was used a microcontroller TIVA TM4C123G, connected to a SIM900 GSM module and a NEO 6M GPS module to recover the vehicle position. The technology used to transmit data between the software and the hardware was SMS. For the tests, it was used a DC motor with reduction gearbox to drive the simulation of electric windows, a servo motor Tower Pro SG-5010 to drive the simulation of electric locks, and PIR sensor connected to a speaker to simulate an alarm. Thus, the developed software for Android smartphone could control, from distance, the engines that simulated the windows and power locks as well as receiving a notification if the PIR sensor was triggered. Already the GSM module connected to the microcontroller also sent to each preset time interval the coordinates of longitude/latitude captured by the GPS module.